Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/scs.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Rhinopharyngeal Isolated Argyria Induced by Silver-Containing Nasal Drug

Abstract: Localized nasal argyria has been reported in 3 published articles as secondary to occupational exposure and involving the anterior part of the nose. No previous cases of such pathology involving the rhinopharynx were described. Here we report the first case of localized argyria of the roof and of the posterior wall of the rhinopharynx secondary to prolonged use of nasal drops containing colloidal silver protein. The recognition of such pathology can be useful to increase the number of conditions that must be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Research into the safety profile of CS is limited mainly to animal models and case reports [ 21 ]. Indiscriminant use of silver can cause argyria, which is a permanent blue-grey discoloration of the skin, mucosa or internal organs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research into the safety profile of CS is limited mainly to animal models and case reports [ 21 ]. Indiscriminant use of silver can cause argyria, which is a permanent blue-grey discoloration of the skin, mucosa or internal organs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As nasal drops of nanosilver colloids are commonly used to treat rhinitis clinically (Burgert, 2014;Raimondo et al, 2014), this introduces another unconventional way for AgNP exposure to human beings. On one hand, the olfactory receptor cells are in direct contact with both the environment and the central nervous system and the olfactory pathway offers a potential approach for targeting the brain, thus circumventing the blood-brain barrier.…”
mentioning
confidence: 99%
“…It was concluded that skin argyria is a consequence of the long-term intake of silver preparations into the body both from the inside (through the stomach) and from the outside (ingrained silver dust). Subsequently, cases of skin argyria were noted with the use of silver drugs (silver nitrate, collargol, and protargol) [30][31][32][33]. Thus, professional and medicinal skin argyria were distinguished [30].…”
Section: Introductionmentioning
confidence: 99%